Electrolyte Effects on the Stability of Ni−Mo Cathodes for the Hydrogen Evolution Reaction. Issue 15 (26th June 2019) - Wijten, Jochem H. J.; Riemersma, Romy L.; Gauthier, Joseph; Mandemaker, Laurens D. B.; Verhoeven, M. W. G. M. (Tiny); Hofmann, Jan P.; Chan, Karen; Weckhuysen, Bert M.
Abstract: Water electrolysis to form hydrogen as a solar fuel requires highly effective catalysts. In this work, theoretical and experimental studies are performed on the activity and stability of Ni−Mo cathodes for this reaction. Density functional theory studies show various Ni−Mo facets to be active for the hydrogen evolution reaction, Ni segregation to be thermodynamically favorable, and Mo vacancy formation to be favorable even without an applied potential. Electrolyte effects on the long‐term stability of Ni−Mo cathodes are determined. Ni−Mo is compared before and after up to 100 h of continuous operation. It is shown that Ni−Mo is unstable in alkaline media, owing to Mo leaching in the form of MoO4 2−, ultimately leading to a decrease in absolute overpotential. It is found that the electrolyte, the alkali cations, and the pH all influence Mo leaching. Changing the cation in the electrolyte from Li to Na to K influences the surface segregation of Mo and pushes the reaction towards Mo dissolution. Decreasing the pH decreases the OH − concentration and in this manner inhibits Mo leaching. Of the electrolytes studied, in terms of stability, the best to use is LiOH at pH 13. Thus, a mechanism for Mo leaching is presented alongside ways to influence the stability and make the Ni−Mo material more viable for renewable energy storage in chemical bonds. Abstract : Leaching out from here : The stability of Ni−Mo cathodes for the electrocatalytic production of hydrogen from water has been explored in alkaline electrolytes. Both experimental and theoretical methods are used to gain physicochemical insights into the underlying reasons for Mo leaching. This leaching is found to be a function of the chemical nature of the electrolytes used.